Pathogenesis of vascular dysfunction and cellular senescence in carotid disease in diabetic patients; A literature review. Issue 1 (2021) - Eleni, Sertedaki; Zografos, George; Veroutis, Dimitris; Sigala, Fragiska; Zagouri, Flora; Galyfos, George
No abstract available